If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2p + 4)(3p + -3) = 0 Reorder the terms: (4 + 2p)(3p + -3) = 0 Reorder the terms: (4 + 2p)(-3 + 3p) = 0 Multiply (4 + 2p) * (-3 + 3p) (4(-3 + 3p) + 2p * (-3 + 3p)) = 0 ((-3 * 4 + 3p * 4) + 2p * (-3 + 3p)) = 0 ((-12 + 12p) + 2p * (-3 + 3p)) = 0 (-12 + 12p + (-3 * 2p + 3p * 2p)) = 0 (-12 + 12p + (-6p + 6p2)) = 0 Combine like terms: 12p + -6p = 6p (-12 + 6p + 6p2) = 0 Solving -12 + 6p + 6p2 = 0 Solving for variable 'p'. Factor out the Greatest Common Factor (GCF), '6'. 6(-2 + p + p2) = 0 Factor a trinomial. 6((-2 + -1p)(1 + -1p)) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(-2 + -1p)' equal to zero and attempt to solve: Simplifying -2 + -1p = 0 Solving -2 + -1p = 0 Move all terms containing p to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1p = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1p = 0 + 2 -1p = 0 + 2 Combine like terms: 0 + 2 = 2 -1p = 2 Divide each side by '-1'. p = -2 Simplifying p = -2Subproblem 2
Set the factor '(1 + -1p)' equal to zero and attempt to solve: Simplifying 1 + -1p = 0 Solving 1 + -1p = 0 Move all terms containing p to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1p = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1p = 0 + -1 -1p = 0 + -1 Combine like terms: 0 + -1 = -1 -1p = -1 Divide each side by '-1'. p = 1 Simplifying p = 1Solution
p = {-2, 1}
| 3x+x^2+5=0 | | f(n)=280+25n | | 3x^4-24x= | | 3x+x^2+35=0 | | -5m+10=40 | | 15-3n=2.7 | | 3a^2-3a-81=9 | | x^2-23x+132=0 | | 39.99+0.45(x)=62.49 | | 5n^2-12n-32=0 | | 16x^2-56x+0=0 | | 7+8(t-1)=6(t+9)+5 | | 4x+10=5x-20 | | 26-4g=12 | | 9n^2+10=46 | | 26-4x=12 | | 8x+14=6x+36 | | 63x^2+76x+21=0 | | 2m+3=3m-3 | | 6(p-4)=-30p | | 2y+18=42 | | (y+9)2=42 | | 3-2(4x-3)=5x-(7+x)-12x | | 6(x+1)=4x+11 | | 2y+4=6y-5 | | 25=3h-5 | | 3n-2=7n | | 3(2a-7)=9 | | 3x+14=2x-9 | | 3(1-3x)+4=5(x+2) | | 2m^2-5m-12= | | y=7x^2-11x+9 |